Completely contractive maps between C*-algebras - W. T. Sulaiman (International Journal of Mathematics and Mathematical Sciences)
We give a simple proof that any completely contractive map between C*-algebras is the top right hand corner of a two completely positive unital matrix operator. Some well-known results are deduced.